2007
DOI: 10.1111/j.1360-0443.2006.01693.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and socio‐economic distribution of hazardous patterns of alcohol drinking: study of alcohol consumption in men aged 25–54 years in Izhevsk, Russia

Abstract: AimTo estimate the prevalence of hazardous drinking and its socio-economic distribution among Russian men. Design Participants were an age-stratified, population-based random sample of men aged 25-54 years living in Izhevsk, a city in the Urals, Russia. Interviewers administered questionnaires to cohabiting proxy respondents about behavioural indicators of hazardous drinking derived from frequency of hangover, frequency of drinking beverage spirits, episodes in the last year of extended periods of drunkenness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 33 publications
5
97
3
2
Order By: Relevance
“…A study from Russia found that 75% of the men drank spirits [13], while a Thailand study which was done among subjects who were aged 12-65 years, showed the prevalence of current drinkers to be 28.6% [14]. A study which was done in Finland showed the prevalence of hazardous drinking to be 5.8% [15].…”
Section: Methodsmentioning
confidence: 99%
“…A study from Russia found that 75% of the men drank spirits [13], while a Thailand study which was done among subjects who were aged 12-65 years, showed the prevalence of current drinkers to be 28.6% [14]. A study which was done in Finland showed the prevalence of hazardous drinking to be 5.8% [15].…”
Section: Methodsmentioning
confidence: 99%
“…This, again, appears to be concentrated among young men, consistent with prior literature from the Russian financial crisis and other economic downturns, during which men at high risk of unemployment, and with low social support, were at highest risk of alcohol abuse and dependence. 191 By contrast, evidence for the relationship between recessions and chronic health conditions has important methodological limitations. Given that these conditions and their exacerbations take a long time to manifest, it is not surprising that studies that have tried to account for previous health have failed to find strong evidence that these conditions are affected by recessions.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of tobacco use are also very high in Russia (Perlman et al 2007). Economic difficulties and lower educational status appear to increase these negative practices (Perlman 2010;Tomkins et al 2007). …”
Section: Migration and Health In Russiamentioning
confidence: 99%